2009
DOI: 10.1111/j.1447-0756.2009.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased interaction between heat shock protein 27 and mitogen‐activated protein kinase (p38 and extracellular signal‐regulated kinase) in pre‐eclamptic placentas

Abstract: The interaction between Hsp27 and MAPK was increased, suggesting that phosphorylation of Hsp27 might be induced by p38 and ERK in placentas from patients with pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…In keeping with our data, miR-377 expression was found to be up-regulated in fibroblast cell lines under growth arrest, and its expression is reported to be negatively correlated with that of promitogenic signaling molecules (41). Both trophoblast proliferation (1) and ERK expression (42) are altered in placentas from pregnancies complicated by pre-eclampsia; thus, it is tempting to Pre-miR-145 (500 nM) was transfected into first trimester placental explants. 48 h later, total RNA was extracted, and mRNA expression of multiple genes was assessed using PCR pathway arrays.…”
Section: Discussionmentioning
confidence: 49%
“…In keeping with our data, miR-377 expression was found to be up-regulated in fibroblast cell lines under growth arrest, and its expression is reported to be negatively correlated with that of promitogenic signaling molecules (41). Both trophoblast proliferation (1) and ERK expression (42) are altered in placentas from pregnancies complicated by pre-eclampsia; thus, it is tempting to Pre-miR-145 (500 nM) was transfected into first trimester placental explants. 48 h later, total RNA was extracted, and mRNA expression of multiple genes was assessed using PCR pathway arrays.…”
Section: Discussionmentioning
confidence: 49%
“…The preeclamptic pregnancy is the most studied among pregnancy-specific complications due to its strong association stress which can result into endothelial dysfunction. Hsp70 and Hsp27 are well-known stress response proteins expressed under various pathological conditions, including trauma, and focal or global ischemia (37). The present study demonstrated that Hsp70 and Hsp27 proteins were increased in preeclamptic women.…”
Section: Discussionsupporting
confidence: 50%
“…Studies have shown that Hsp70 levels in pregnant women are significantly higher than those in healthy pregnant women (18,19). It is also known that placental levels of Hsp27 in normal patients are lower than those in patients with preeclampsia (20).…”
Section: Introductionmentioning
confidence: 99%
“…It encodes for a small protein (17 kDa) and has been reported to be implicated in cell cycle arrest, apoptosis, DNA repair, and the maintenance of genomic stability via the activation of several downstream stress response proteins such as the p38/JNK kinases (Amanullah et al 2003;Bulavin et al 2003;Gupta et al 2006;Hollander et al 1999;Tront et al 2006;Zerbini et al 2004). Interestingly, the stress-responsive p38 MAPK pathway is reported to be robustly activated in PE (Shin et al 2009) and is essential to oxidative stress-mediated placental dysfunction (Cindrova-Davies et al 2007). However, few data are available on the potential function of Gadd45α in the process of placental oxidative stress.…”
Section: Introductionmentioning
confidence: 95%